A benign or malignant eyelid lump – can you tell? An unusual collision tumour highlighting the difficulty differentiating a hidrocystoma from a basal cell carcinoma. (28th June 2012) - Jayaprakasam, Anuradha; Rene, Cornelius
Abstract : Hidrocystoma and basal cell carcinoma (BCC) are common eyelid lesions. The former is benign while the latter is malignant and can cause significant destruction of the adnexal structures, orbital invasion and visual loss. The authors describe a case of a 76-year-old female with a slow growing right upper lid lesion which was diagnosed as a hidrocystoma but excision biopsy revealed a collision tumour comprised of a BCC abutting a hidrocystoma in the same lesion. Cystic BCC can masquerade as hidrocystoma but there are no previous case reports of BCC coexisting with hidrocystoma in the same lesion. This case highlights the fact that apparently benign lesions, such as hidrocystomas, may actually be malignant or coexist with malignant pathology. Clinicians should have a low threshold for appropriate excision biopsy and histological examination of such lesions, especially if there are sinister features, such as lash loss, induration, pigmentation or a pearly appearance.